Sebaceous breast carcinoma - Natália Nobre de Alencar; Diego Agra de Souza; Alexandre Alves Lourenço; Raimunda Ribeiro da Silva (Autopsy and Case Reports, 2022)
Breast sebaceous carcinoma is one of the rarest breast neoplasms, with less than 30 cases reported worldwide. Due to the rarity, the new WHO classification of breast tumors grouped these tumors among the ductal carcinoma. A detailed description of these cases is relevant due to the insufficient knowledge about the prognosis of this neoplasm. We report the clinical, histological, and immunohistochemical characteristics of a case of sebaceous carcinoma of the breast in an 81-year-old woman with a right breast nodule. The tumor was composed of nests of a varying mixture of sebaceous cells with abundant slightly vacuolated cytoplasm, surrounded by smaller oval-to-fusiform cells with eosinophilic cytoplasm without vacuolization. No lymph node metastases were present. The immunohistochemical reactions were positive for GATA3, EMA, CD15, and GCDFP15 (focal staining), and negative for RE, RP, and HER-2. The tumor was classified as triple-negative. Morphologically, the differential diagnoses included skin sebaceous carcinoma, lipid-rich carcinoma, apocrine carcinoma, and glycogen-rich clear cell carcinoma. Most of the previously reported cases were positive for RE and RP, which generally was associated with a better prognosis. However, some cases presented a more aggressive behavior with distant and lymph node metastases.